Injures of spermatogenesis epithelium of testis are caused by action of chronical hyperthermia - Pastukhova V. A. (Морфологія, 2009)
The goal of the current research was to estimate the kind of morphological changes in testicles of white rats in chronic hyperthermia of medium degree. The testicles of senior rats, which were exposed to the temperature of 42,0-43,1°C for 5 hours daily during 60 days (medium-degree hyperthermia), served as the material for the research. The serious damages of spermatogenesis occur in testis of experimental animals by influence of common hyperthermia of middle stage, that caused by layer’s necrosis of spermatogenesis epithelial cells. Don’t mention on common pathogenesis changes in structure organization of seminiferous tubules plots stay with little changes in substations, that supply update processes of spermatogenesis.